2021
DOI: 10.1371/journal.pone.0257035
|View full text |Cite
|
Sign up to set email alerts
|

Development and usability testing of mobile application on diet and oral health

Abstract: In several nations, caries in pre-school children remain a significant oral health issue. In an outbreak period such as the Coronavirus disease 2019 (COVID-19), remote contact and education aimed at the prevention of oral diseases and the preservation of children’s oral health are more relevant than ever. Currently, the amount of published applications is far higher than the published scientific studies while the problems of usability remains vulnerable. The goal of this paper was to comprehensively document t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
0
12
0
2
Order By: Relevance
“…was critical [ 29 ]. Other studies have also concluded that the oral-health-related mobile apps improve oral hygiene [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…was critical [ 29 ]. Other studies have also concluded that the oral-health-related mobile apps improve oral hygiene [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Designing and developing an mHealth app using the user-centered element by involving the users in all stages has its robustness and is a gold standard approach in accomplishing mHealth apps that are useful, easy to use, and satisfying to the users [ 30 ]. For example, an mHealth app on the diet and oral health for parents of preschool children, which was developed based on their needs, included information on how to prevent oral disease in their children and has been scored with good usability [ 31 ]. UCD requires an iterative design process to understand and internalize the users’ needs, goals, strengths, limitations, contexts, and intuitive processes [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of oral health education, nutrition and diet should be included in a global health program as they constitute common risk factors for non-communicable diseases [ 71 , 72 ]. Reviews of the literature have concluded that the use of nutrition-related mobile applications increases knowledge and improves behavior [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%